CARACTERISATION ET FONCTION DE LA REPRODUCTION CHEZ LE DROMADAIRE D’ALGERIE - GHERISSI Djallel Eddine (My University, 2019)
Abstract The dromedary camel is a pseudoruminant adapted to arid climates, which has the physiological, biological and metabolic peculiarities that give it a legendary reputation to survive, reproduce and produce in the extreme conditions of the desert environment considered restrictive for other ruminants. The objectives of this study are: (1) To describe dromedary management practices and their reproductive performance in existing breeding systems, (2) To study gonadal function in male dromedaries, (3) To study the female camel genital tract in different physiological and pathological statuses. The two breeding methods found in the study area are pastoral and sedentary. They are divided into four systems; transhumant (27%), semi-intensive (61.11%), agro-pastoral (2.78%) and semi-nomadic (8%). In the arid environment, the dromedary is an excellent polyfunctional animal. Specific activities are identified with each type of livestock systems.The reproductive performance survey revealed low levels of fertility (birth-first calving = 3.81 ± 1.20 years, Calving - Calving interval = 22.92 ± 8.16 months). Lack of pasture, lack of manpower and low capital are the main constraints to the production of camel farms. The adult male camel showed significant seasonal changes of their testicular histomorphometry for both exocrine and endocrine compartments which they significantly explaining biometric variations, as well as plasma concentrations of sex steroids and epididymal sperm reserve. Similarly, hematology and blood biochemistry suggest the action of hydroelectrolytic balance, nutrition, well-being, BCI, stress, degree of physical activity, hormonal status, and environmental factors of extreme aridity on homeostatic balance around the rutting season. In female camels, a high level of folliculogenesis, expressed by a high frequency of active ovarian structures, low levels of inactive ovaries and a high proportion of females with ovaries showing medium-sized or ovulatory follicles (68.8% - 75%) is observed between November and June, but without cessation of ovarian activity during the dry season. They present a flexible reproduction strategy influenced by age, body index and seasons. In other hand, single and multiple linear regression formulas are generated to help estimate gestational age. BPD (biparietal diameter) gaves the most accurate prediction (R2 = 0.99, P <0.001, SEpred = 1.24 days). Finally, the prevalence of she-camels with pathologies of their genital tract was 20%. The total number of identified abnormalities was 41. These conditions are ranked in descending order of incidence by: ovarian diseases (48.8%), uterus abnormalities (21.1%), ovarian bursa pathologies (18.2%), oviduct affections (18.2%), adhesions (15.2%) and pathology of the cervix (3%). The number of females presenting the association of two or three pathologies was 6, ie a prevalence of 3.6%. Finally, each pathological entity has been accompanied by an exhaustive histopathological description. ------------------------------------------------- الملخص الجمل العربي حيوان شبه مجترة تكيف مع المناخات الجافة، لديه الخصائص الفسيولوجية والبيولوجية والاستقلابية التي تمنحه سمعة أسطورية من أجل البقاء والأنتاج في الظروف القاسية للبيئة الصحراوية، وهو ما يعتبر تقييدا للحيوانات المجترة الأخرى. تم تحديد الأهداف التالية : (1) وصف ممارسات تربية الإبل في النظم المستقرة والرعوية، (2) تقدير الأداء التناسلي في البيئة الطبيعية للجمل العربي، (3) وصف العلاقة بين الظروف الموسمية والمحلية لنشاط الغدد التناسلية في ذكور وإناث الجمل العربي، (4) وتقدير عمر الحمل في نوق الحوامل وأحصاء أمراض الجهاز التناسلي. تم الكشف من خلال هذه الدراسة على نمطين لتربية الإبل: الرعوي والمستقر. وتنقسم هذه الأنماط ألى أربع نظم؛ الأنتجاع (27٪)، البدو الرحل (8٪) ، شبه المكثف (61.11٪) والزراعي الحيواني (2.78٪). و تم أظهارأن الجمل حيوان متعدد الوظائف بامتيازفي البيئة القاحلة مع تحديد أدوارخاصة بكل نظام من الأنظمة المحلية لتربية الأبل. وكشفت الدراسة الاستقصائية عن الأداء التناسلي ذو مستويات منخفضة من الخصوبة ( الوقت لولادة النوق البكرة = 3.81 ± 1.20 سنة ، الوقت بين الولادة و الولادة = 22.92 ± 8.16 شهرً ا). إن نقص المراعي ونقص اليد العاملة وانخفاض رأس المال هم العوائق الرئيسية أمام إنتاج مزارع الإبل. و كشفت دراسة وظاىف الغدد التناسلية الموسمية في الذكور البالغين عن تغيرات موسمية في القياسات النسيجية للخصيتين ومنه تم بشكل ملحوظ شرح الاختلافات البيومترية وكذلك تركيزات البلازما من الهرمونات الجنسية واحتياطي الحيوانات المنوية البربخية. و كذلك تشيرهذه الدراسة ألى تأثرالتحاليل الدموية والكيميائية الحيوية للدم بالتوازن الكهرمائي ، التغذية، مستوى الراحة ، درجة النشاط البدني، الجفاف الشديد وذلك حول موسم التكاثر. و في إناث الأبل، تم تسجيل مستوى عال من تكوين الجريبات خلال الفترة من نوفمبر إلى يونيو ، حيث تم التعبير عن ذلك من خلال تواتر مرتفع لمختلف المكونات المبيضية النشطة ، وانخفاض في مستويات المبايض غير النشطة ، ونسبة عالية من الإناث مع المبيضات ذات الجريبات المتوسطة أو التبويضية (68.8% -75%). وخلال الربيع والشتاء كانت نسبة الإبل ذات الجريبات الكيسية (30.6% ضد 17.4%) والأجسام الصفراء (62.5% ضد 40.3%) عالية. يشير التغير في تواتر المكونات المبيضية المختلفة وفقا لمختلف الأعمار والمواسم إلى أن نشاط المبيض أعلى عند الإناث الأكبر سنا وفي الإناث ذات مؤشر جسمي أعلى. بالنسبة للإناث الحوامل ، أعطت المعاملات البيومترية الجنينية أفضل صيغ الانحدار لتقدير عمر الحمل. حيث قدمت صيغة الانحدار التدريجي باستخدام BPD (قطر ثنائي القطبية) التنبؤ الأكثر دقة (R2 = 0.99, P <0.001, SEpred = 1.24 jours). النتائج التي تم الحصول عليها يمكن أن تساعد الممارسين في التقدير السريع لعمر الجنين خلال الفحص بالموجات فوق الصوتية ،عند دراسة الأجنة المجهضة ، في حالة الخداج ،و في البحث العلمي على التكاثر وتطوير الإبل. و أخيرًا، بلغ معدل انتشار أمراض الجهاز التناسلي للنوق 20٪. العدد الإجمالي للأمراض التي تم تحديدها هو 41 ، و منه نسبة وقوع هذه الأمراض تقدر بـ 124.2 ٪. يتم تصنيف هذه الأمراض حسب الترتيب التنازلي للوقوع ألى: أمراض المبيض (48.8%)، أمراض الرحم (21.1 ٪) ، أمراض حافظات المبيض (18.2 ٪)، أمراض قناة البيض (18.2%) ، الألتصاقات (15.2 ٪) وأمراض عنق الرحم (3%) . ويبلغ عدد الإناث اللواتي أظهرن ارتباط اثنين أو ثلاثة من الأمراض 6 أي بنسبة 3.6٪. وأخيرًا، تمت مرافقة كل مرض للجهازالتناسلي بعيينات من خلالها تم القيام بتشريح مرضي ووصف شامل لأمراض الأنسجة. -------------------------------------------------- Résumé Le dromadaire, un pseudo-ruminant adapté aux climats arides, dispose des particularités physiologiques, biologiques et métaboliques qui lui confèrent une réputation légendaire à survivre, se reproduire et produire dans les conditions extrêmes du milieu désertique considérées restrictives pour les autres ruminants. Cette étude a comme objectifs : (1) Décrire les pratiques de gestion de l’espèce cameline et leurs performances de reproduction dans les systèmes d’élevage existants, (2) Etudier la fonction gonadique chez le dromadaire mâle, (3) Etudier l’appareil génital des chamelles en différents statuts physiologiques et pathologiques. Les deux modes d’élevage rencontrés dans la région d’étude sont le pastoral et le sédentaire. Ils sont répartis en quatre systèmes ; le transhumant (27%), le semi-nomadique (8%), le semi-intensif (61,11%) et l’agro-pastoral (2,78%). Le dromadaire exprime une excellente poly-fonctionnalité avec des activités spécifiques identifiées au sien de chaque type d’élevage. L’enquête sur les performances de la reproduction révéle de faibles niveaux de fécondité (naissance-chamelage = 3,81±1,20 ans, intervalle chamelage-chamelage= 22,92±8,16 mois). Le manque de pâturage, le manque de main-d'œuvre et le faible capital financier constituent les principales contraintes à la production des élevages camelins. Les gonades des dromadaires mâles adultes révèlent des changements histomorphométriques saisonniers des deux compartiments exocrine et endocrine, expliquant significativement les variations biométriques, ainsi que les concentrations plasmatiques en stéroïdes sexuels et la réserve spermatique épididymaire. De même, l’hématologie et la biochimie du sang suggèrent l’action de l’équilibre hydroélectrolytique, la nutrition, le bien être, le BCI, le stress, le degré d'activité physique, le statut hormonal et les facteurs environnementaux d’extrême aridité sur l’équilibre homéostatique aux alentours de la saison de rut. Chez les femelles, un niveau élevé de folliculogenèse, exprimé par une fréquence élevée de structures ovariennes actives, de faibles taux d'ovaires inactifs et une proportion élevée des femelles avec des ovaires présentant des follicules de taille moyenne ou ovulatoires (68,8% - 75%) est constaté entre novembre et juin, mais sans cessation de l’activité ovarienne pendant la saison sèche. Elles présentent une stratégie de reproduction flexible influencée par l'âge et les saisons. Chez les femelles gestantes, des formules de régression linaires simples et multiples sont générer afin d’aider à l’estimation de l’âge de gestation. Le BPD (diamètre bipariétal), a donné la prédiction la plus précise (R2 = 0.99, P <0.001, SEpred = 1.24 jours). Enfin, la prévalence des chamelles présentant des pathologies de leur tractus génital est de 20%. Le nombre total des pathologies recensées est de 41. Ces affections sont classées par ordre décroissant d’incidence en : pathologies ovariennes (48.8%), pathologies de l‘utérus (21,1%), pathologies des bourses ovariennes (18,2%) pathologies des oviductes (18,2%), les adhérences (15,2%) et pathologie du cervix (3%). 6 cas de pathologies associées représente une prévalence de 3,6%. Chacune des entités pathologiques a été accompagnée d’une description histopathologique exhaustive.